'Generation rent' and the emotions of private renting: self-worth, status and insecurity amongst low-income renters. Issue 8 (13th September 2020) - McKee, Kim; Soaita, Adriana Mihaela; Hoolachan, Jennifer
Abstract: The UK private-rented sector is increasingly accommodating a diverse range of households, many of whom are young people struggling to access other forms of housing. For those at the bottom end of the sector, who typically have limited economic resources, it is a precarious housing tenure due to its expense and insecurity, yet few studies have explored qualitatively the emotional consequences of this for well-being. We address this gap in the 'generation rent' literature by focusing attention on those voices that have been less prominent in the literature. Informed by the theoretical lens of 'residential alienation', our study illustrates the emotional toll of private renting upon low-income groups in a national context where state regulation is more limited. In doing so, we add nuance to the literature surrounding socio-economic differentiation within the UK private-rented sector. Our arguments are also relevant to an international audience given global concerns about housing precarity and the politics of housing.